Characteristics of Hercules and Bodhisattva Longmen Grotto statues: a systematic literature review (SLR) - Li, Xiaoshu; Mohd Yusof, Mohd Johari; Ser, Wue Hiong; Perumal, Velu; Wang, Xiufeng (Jomard Publishing, 2022)
Grotto arts is gradually altered due to various reasons, such as time and environmental impact. The Longmen Grottoes, notably in the 2000 World Heritage List, is one of the affected grottoes. Several façades of Longmen Grotto Buddha statues are fading and unrecognisable. Therefore, the original characteristics of these Buddha statues were explored for restoration and reference. First, the exploration of Hercules and Bodhisattva statue characteristics in Longmen Grottoes used a systematic literature review (SLR). Second, Hercules statues in the Northern Wei Dynasty were found to exhibit the Central Plains Style, while the Bodhisattvas in Tang Dynasty bears more resemblance to the façade of “secularisation”. The historical Buddhist and art preservation for prospective appreciation might better be considered as grotto arts, which originated from India and flourished in China, are remarkable treasures clothing and be an essential step to achieving sustainability in the apparel industry.